Management training in small and medium-sized enterprises : methodological and conceptual issues - Wong, Cecilia [Verfasser]; Marshall, J. Neill [Verfasser]; Alderman, Neil [Verfasser]; Thwaites, Alfred [Verfasser] (My University, 1997)
"The paper examines the impact of management training and development on the organisation and performance of small and medium- sized enterprises (SMEs), via a variety of quantitative und qualitative research techniques and including both cross-sectional and longitudinal approaches to analysis. The paper demonstrates the value of management training and development in SMEs and demonstrates a series of one-off and the conditions under which management development project are likely to be more (1990) and Hendry et al. (1991), indicating the factors influencing training within business, and shows the indirect and complex links between management training and firm performance." (authors's abstract, IAB- Doku) Anhand empirischer Untersuchungsergebnisse wird die Bedeutung von Managementtraining und -entwicklung für die Organisation und Leistungsfähigkeit von kleinen und mittleren Unternehmen untersucht. (IAB)
Keywords: Managementtraining; Kleinbetrieb; Mittelbetrieb; Unternehmenserfolg